Answer:
23.76%
Step-by-step explanation:
Answer:
A.
Step-by-step explanation:
Answer:
the answer is c, f(x)=3^x+3
Step-by-step explanation:
i hope this helped
Answer:
2y = x + 2
Step-by-step explanation:
Looking at the graph, we can see from one point to the next (from right to left), the x-value rises by 2 and the y-value by 1;
From this we can work out the gradient between two points using the formula, i.e. the change/difference in y divided by the change/difference in x:
![m = \frac{dy}{dx} = \frac{1}{2}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%5Cfrac%7B1%7D%7B2%7D)
Joining the points gives a straight line, which means a constant gradient of ¹/₂
Use the line equation formula to get the function:
y - y₁ = m(x - x₁)
m = ¹/₂
x₁ = 0
y₁ = 1
y - 1 = ¹/₂.(x - 0)
y - 1 = ¹/₂.x
2y - 2 = x
2y = x + 2